Evaluation and optimal width ratio selection of microbial mineralization technique in the repair of lining cracks in Xinjiang desert open channel - Jianxin Wang; Jianing Zhu; Yusheng Li; Shihao Zhang; Chengming Feng (Scientific Reports)
Abstract The bank slope structure of the open channel in the Xinjiang desert is affected by seasonal climate changes and water erosion, leading to lining cracking. This study identified the optimal culture conditions and mineralization factors for Sporosarcina pasteurii through strain cultivation and precipitation assays. Subsequently, 0.1~5.0 mm wide penetrating concrete cracks were prefabricated, and microbially induced calcium carbonate precipitation (MICP) repair tests were conducted over 16 cycles. These experiments included macroscopic performance evaluations, such as area repair rate, penetration resistance, and capillary water absorption tests, alongside microscopic analyses using X-ray diffraction and scanning electron microscopy. The results indicate that MICP technology effectively repairs narrow cracks, preserving crack surface integrity, significantly reducing permeability and water absorption, and enhancing the durability of the concrete. However, for cracks exceeding 1.0 mm in width, the repair efficiency declines progressively. Based on the experimental data, it is concluded that a crack width of 1.0 mm is the optimal threshold for effective MICP-based repair within 16 cycles, ensuring both structural integrity and optimal waterproofing. These results offer valuable insights into the potential application of MICP technology for the remediation of lining cracks in the bank slopes of water conveyance channels in Xinjiang Desert.